An assessment of the management of sexually transmitted diseases (STDs) in a rural district health ward of Northern Kwazulu - McCoy, David (Department of Paediatrics and Child Health, 2017)
This study is an assessment of the quality of sexually transmitted disease (STD) management and control in a rural district of South Africa. A semi-structured questionnaire was administered to 5 nurses from public sector primary health care clinics, 5 doctors from the public district hospital, 5 private general practitioners, 6 traditional healers and 7 STD patients. A patient simulation exercise involving 6 nurses and 6 general practitioners was also conducted. Using routine data collection forms, the spectrum of STD syndromes and the contact tracing rate were assessed. The private sector treated nearly a third of the STDs even though they charge about ten times the price of the public sector services. In general, the clinical skills of all providers were poor. While hypothetical patient histories produced reasonable responses on STD management during the interviews, the patient simulation results showed that health service providers provided STD management that was much poorer than the questionnaires indicated. The private general practitioners did not practice syndromic STD management and often did not use laboratory tests appropriately resulting in incorrect diagnosis and inappropriate treatment for STDs. All health service providers did not counsel, promote condoms or encourage contact notification adequately. All health service providers were keen to participate in continuing medical education that better equip them to manage STDs. Any attempts at improving the quality of care in the district must therefore include private general practitioners as an important and central component of STD policy and planning. Interviews with traditional healers and patients showed the importance of using non-biomedical constructs of health and illness in developing health promotion strategies. There is an urgent need to improve STD management at district level in an attempt to meet the first milestone of ensuring that a patient presenting with an STD to a health service is correctly managed. This can be done through the design of simple quality assurance methods as demonstrated in this paper.